2008
DOI: 10.1039/b805101a
|View full text |Cite
|
Sign up to set email alerts
|

Covalent surface modification of a metal–organic framework: selective surface engineering via CuI-catalyzed Huisgen cycloaddition

Abstract: A Zn-cornered, mixed-ligand, metal-organic framework (MOF) bearing TMS-protected acetylenes has been constructed and its surface decorated with organic molecules via'click chemistry', in a demonstration of selective post-synthesis functionalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(107 citation statements)
references
References 23 publications
0
102
0
5
Order By: Relevance
“…Most of the previous studies on MOF postsynthetic modification have shown the introduction of only a single chemical modification into the MOF lattice. Very few have demonstrated that more than one chemical reagent could be used to covalently modify a single MOF structure 45,58. In one example, two different anhydrides were used to successfully modify isoreticular metal-organic frame-work-3 (IRMOF-3, Chart 1).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the previous studies on MOF postsynthetic modification have shown the introduction of only a single chemical modification into the MOF lattice. Very few have demonstrated that more than one chemical reagent could be used to covalently modify a single MOF structure 45,58. In one example, two different anhydrides were used to successfully modify isoreticular metal-organic frame-work-3 (IRMOF-3, Chart 1).…”
Section: Introductionmentioning
confidence: 99%
“…The XPS results clearly show the difference in binding energies from azide (a) to the product triazole (b), where no residual azide was detected. The absence of azide nitrogens thus shows that the reaction has proceeded, though it cannot be unambiguously concluded that all azides have reacted to form Beside the above mentioned techniques some of the other techniques that are used for characterizing surface modification of materials are matrix assisted laser desorption/ionization-time of flight (MALDI-TOF), [66,67] size-exclusion chromatography (SEC), [68] cyclic voltammetry, [69] contact angle measurement, [70] UV-vis spectroscopy, [60] and confocal microscopy, [49] Auger electron spectroscopy, [71,72] and secondary ion mass spectrometry (SIMS). [73] …”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 99%
“…Gadzikwa et al [67] constructed a Zn-cornered, mixed-ligand, MOF bearing silane protected acetylene bonds that could be deprotected by using conventional organic chemistry. Such functionality would provide an extra level of control over the subsequent copper catalyzed azide alkyne coupling as Cu(I) catalyzes addition to terminal alkynes exclusively and it can be controlled where the cycloaddition occurs by selective deprotection.…”
Section: Miscellaneous Surfacesmentioning
confidence: 99%
“…Typically PSM is applied using covalent interactions with the guest and the MOF's framework, however non-covalent interactions may be used as well [17]. When employing covalent interactions, there is large variety of organic reactions available; for example PSM has been applied for amide coupling [18], imine condensation [19,20], urea formation [21,22], bromination [23], N-alkylation [24], and click reactions [25,26]. Several of these PSM methods described have been demonstrated for MOF membranes/thin films in the literature.…”
Section: Introductionmentioning
confidence: 99%